A Note on Optimal Stopping in Models with Delay - Pavel V. Gapeev; M. Reiß (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
We consider an optimal stopping problem in a certain model described by a stochastic delay differential equation. We reduce the initial problem to a free-boundary problem of parabolic type and prove the corresponding verification assertion. We also give an example of such an optimal stopping problem related to mathematical finance.
urn:nbn:de:kobv:11-10050820
Keywords: 330; Suchtheorie; Stochastischer Prozess; Theorie; stochastic delay differential equation